Dampak Profesi Ojek Online Bagi Perekonomian Driver Ojek Online - Ramadhika Darmaputra; Ryan Hidayat; Jaja Nurjana; Wahidah R. Bulan; Yuliani Widianingsih; Ronald Manolu (Jurnal Manajemen Riset Inovasi, 2024)
The emergence of online transportation services has changed the way humans access areas of life, increasing accessibility significantly. The integration of digital technology has brought increased speed, efficiency and connectivity to services, especially through applications on smartphones. For example, online motorcycle taxi services in Indonesia have become an important source of income for many individuals. Many people rely on work as online motorcycle taxi drivers to meet their family's economic needs. This research aims to provide a comprehensive picture of the role of online motorcycle taxis as a source of income, taking into account the diversity of drivers from various backgrounds, including those with families, those without families, and female drivers. This research uses a qualitative approach, a method suitable for exploring the condition of natural objects. The results of this research are based on interviews with 8 sources from online motorcycle taxi drivers around UPN "Veteran" Jakarta, Pondok Labu Campus. Interviewees involved a variety of backgrounds, and the responses received varied, some were satisfied with their work, while others saw it as just a side job. Even though online motorcycle taxis offer accessibility and flexibility in working hours, research findings show that this profession has not become the main job for most drivers. Tight competition in the online motorcycle taxi industry is also a factor that contributes to the economic constraints felt by some drivers, especially those who have family responsibilities.